Using multivariate techniques to assess the effects of raw material, flaking behavior and tool manufacture on assemblage variability: An example from the late Middle Paleolithic of the European Plain. (November 2017) - Weiss, Marcel; Otcherednoy, Aleksander; Wiśniewski, Andrzej
Abstract: The late Middle Paleolithic in central and eastern Europe is defined by the presence or absence of certain bifacial tools and blank production methods. Hence, the assemblages between MIS 5a and MIS 3 are classified as Mousterian, Taubachian, Micoquian, Micoquo-Prondnikien, Prądnik cycle and Keilmessergruppen, among others. We like to address here the questions of what do these assemblages look like when the type fossils (" fossil directeur ") are set aside and what are the main drivers of variability within and between these assemblages. Therefore, we analyzed nine assemblages of four late Middle Paleolithic open-air sites of the European Plain: Pouch and Königsaue for central Germany, Wrocław-Hallera Av. for southwestern Poland and Khotylevo I-6-2 for western Russia. Our study is based on an attribute analysis of flakes, as they are the most numerous artifact type in the lithic assemblages, bearing traces of the flaking technology in their morphology. Linear and nonlinear multivariate statistical analyses of the flake attributes show similar patterns for the assemblages and show no distinctions between Mousterian and Micoquian assemblages aside from the type fossils. Additionally, assemblage variability is, except for one case, not site specific or regional. The analysis of the factors that drive within and between assemblage variability revealed that the assemblages are influenced by site preservation, raw material size and economy, as well as similar blank production and tool manufacture methods that are present in varying degrees in each assemblage. In other words, taking into account site preservation, the overall character of these late Middle Paleolithic assemblages primarily reflects the flexible application of late Neanderthal flaking and tool production methods to the local raw material constraints. Once the type fossils are removed, these assemblages represent a range of variability that cannot be grouped readily into named archaeological entities that could represent distinct human groups. Highlights: We apply multivariate methods to explore late Middle Paleolithic assemblage variability. We explore factors that explain the variability of flake attributes and assemblages. We explore assemblage variability when type fossils are removed. Grouping the assemblages into named archaeological entities is not meaningful. Variability is influenced by raw material, flaking behavior and tool production.